2006
DOI: 10.1159/000096339
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Percutaneous Access Point Number and Location on Complication and Success Rates in Percutaneous Nephrolithotomy

Abstract: Objectives: Percutaneous nephrolithotomy (PNL) is sometimes associated with complications, especially in patients with complex stones. Herein, we review our experience with PNL to determine the impact of percutaneous access number and location on success and complication rates. Patients and Methods: During a 2-year period, a total of 275 patients with a mean age of 42.3 ± 14.8 (range: 13–75) years underwent PNL. Stones were classified as simple in 51.6%, and complex (staghorn calculi or renal pelvis stones coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 45 publications
3
45
1
3
Order By: Relevance
“…In our study most common location of the stones were 22 Average operating time was 78 minutes for 60 PCNL cases, out of which mean operating time for single stones was 52 minutes (range 45-60 minutes), multiple stones was 70 minutes (range 60-90 minutes) and for staghorn 110 minutes (range 90-120 minutes). Patients with large renal stones needed blood transfusions (Table 4).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…In our study most common location of the stones were 22 Average operating time was 78 minutes for 60 PCNL cases, out of which mean operating time for single stones was 52 minutes (range 45-60 minutes), multiple stones was 70 minutes (range 60-90 minutes) and for staghorn 110 minutes (range 90-120 minutes). Patients with large renal stones needed blood transfusions (Table 4).…”
Section: Resultsmentioning
confidence: 58%
“…20 The major concern in PCNL surgery involves serious postoperative complications such as blood loss, adjacent organ injuries and life threatening infection. 21,22 Lee et al reported the complications of PCNL in 582 patients, they report major complications in 6.8% and minor complications in more than 50% with 11.2% requiring blood transfusion. 23 In study by Osman et al, the complication rate was 50.8% with the most common complication being transient pyrexia in 27.6%, however we report 8% transient post-operative pyrexia and this is explained by the restriction to the selection of patients with preoperative documentation of absence of infection or one week antibiotic treatment according to sensitivity in case of presence of urinary tract organism.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding was found in 39.1% and 7.5% of patients managed with supracostal access and subcostal access, respectively (P < 0.01). Puncture to upper calices can cause injury of posterior segmental artery braches, leading to increased risk of bleeding (24). Akman et al reported similar results; the number of access points was detected as an independent predictive factor for bleeding in multivariate analysis.…”
Section: Discussionmentioning
confidence: 74%
“…There were 63 supracostal punctures which work out to 38% of all punctures. In a study by Yadav R et al Supracostal access was obtained in 332 (37.3%) out of 890 PCNL [14]. In a study by Sukumar S et al 565 patients underwent PCNL, of whom 110 (19.5%) had a supracostal access [15].…”
Section: Discussionmentioning
confidence: 99%
“…The 93.5% includes three patients with CIRF also. When success rates after multiple interventions was analyzed by Aron et al in 2005 with combined approach a total success rate of 94% (including 4 renal units with insignificant residue) was achieved [17].…”
Section: Discussionmentioning
confidence: 99%